CENTRAL KALIMANTAN’S FAST GROWING SPECIES: SUITABILITY FOR PULP AND PAPER - Danang Sudarwoko Adi; Ika Wahyuni; Lucky Risanto; Sri Rulliaty; Euis Hermiati; Wahyu Dwianto; Takashi Watanabe (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2016)
Recent studies of fast growing species grown in PT. Sari Bumi Kusuma, Central Kalimantan, show that based on their fiber dimensions there are five species, namely Endospermum diadenum, Dillenia spp., Adinandra dumosa, Adiandra sp., and Nauclea junghuhnii with good potential for pulp and paper production. The fiber length of those five wood species are was more than 2,200 µm on average. This paper studies the physical properties, fiber dimensions and their chemical contents to predict the paper and pulp quality. The result shows that all of the species were classified in the medium to high density category. All species were classified into the first class quality for pulp and paper. Based on chemical contents, Dillenia sp. is the most suitable species due to its high value of holocellulose and a-cellulose, low lignin content, and its fiber length is about 3,119 µm on average. A. dumosa also has good opportunities because it had the longest fiber lengths (3,137 µm on average) and high value of holocellulose, even though it has the highest lignin content. While Nuclea junghuhnii is less suitable due to low values of holocellulose and a-cellulose.